MiR-29a Knockout Aggravates Neurological Damage by Pre-polarizing M1 Microglia in Experimental Rat Models of Acute Stroke - Zhao, Fangfang; Zhao, Haiping; Fan, Junfen; Wang, Rongliang; Han, Ziping; Tao, Zhen; Zheng, Yangmin; Yan, Feng; Huang, Yuyou; Yu, Lei; Zhang, Xu; Qi, Xiaolong; et al. (Frontiers in Genetics, 2021)
Objective: By exploring the effects of miR-29a-5p knockout on neurological damage after acute ischemic stroke, we aim to deepen understanding of the molecular mechanisms of post-ischemic injury and thus provide new ideas for the treatment of ischemic brain injury. Methods: miR-29a-5p knockout rats and wildtype SD rats were subjected to transient middle cerebral artery occlusion (MCAO). miR-29a levels in plasma, cortex and basal ganglia of ischemic rats, and in plasma and neutrophils of ischemic stroke patients, as well as hypoxic glial cells were detected by real-time PCR. The infarct volume was detected by TTC staining and the activation of astrocytes and microglia was detected by western blotting. Results: The expression of miR-29a-5p was decreased in parallel in blood and brain tissue of rat MCAO models. Besides, miR-29a-5p levels were reduced in the peripheral blood of acute stroke patients. Knockout of miR-29a enhanced infarct volume of the MCAO rat model, and miR-29a knockout showed M1 polarization of microglia in the MCAO rat brain. miR-29a knockout in rats after MCAO promoted astrocyte proliferation and increased glutamate release. Conclusion: Knockout of miR-29a in rats promoted M1 microglial polarization and increased glutamate release, thereby aggravating neurological damage in experimental stroke rat models.